UiTM English language lecturers’ perceptions on the usage of mobile technology devices in teaching practices / Wan Nazihah Wan Mohamed, Zurina Ismail and Muhammad Saiful Anuar Yusoff - Wan Mohamed, Wan Nazihah; Ismail, Zurina; Yusoff, Muhammad Saiful Anuar (2018)
The application of technology is inevitable since its function is to develop and expand humans’ potential to accomplish their daily work. Currently, educational institutions are also in the practice of integrating technology into its teaching and learning activities. The development and utilization of mobile technology devices in teaching and learning practices seems to be prevalent due to the introduction of mobile learning concept. Making use of mobile technology devices like smartphones, mobile learning allows portable learning surroundings that permit the learners to retrieve resources beyond the traditional classroom practices. Nevertheless, its application will only be successful if the students and instructors of educational institutions recognize and utilize these technologies. The use of mobile learning has led to the utilization of mobile technology devices into teaching and learning activities which support spontaneous, personalized and flexible type of learning. The institutions are expected to prepare the next generation of citizens for the technologically oriented global world. As such, institutions need to incorporate educational technology applications in achieving the objectives of producing technologically-enabled students. On top of that, educators in higher learning institutions should consider the possibility of integrating mobile learning in their teaching practices as there is an increase in the number of mobile phone users among students (Supyan, Mohd Radzi, Zaini, & Krish, 2012). Moreover, with the falling pattern in the prices of mobile phones, it is expected that these devices will become affordable to students (Jackman, 2014) which in turn, reduces the need for the institutions to provide computer labs, staff support and servicing bills (Mahendar Kumar & Arpita, 2013). The use of mobile technology devices in teaching and learning seems to be unavoidable (Barreh & Zoraini Wati, 2015; Jackman, 2014). Using mobile technology devices permits portable learning environment which enables learners to access resources at anywhere and anytime (Che, Lin, Jang, Lien, & Tsai, 2009). Although mobile technology devices have been used extensively but its application in education system has not been fully and effectively practiced, specifically in English language learning (Pirasteh & Mirzaeian, 2015).